Sinkhole Stability in Elliptical Cavity under Collapse and Blowout Conditions - Jim Shiau; Suraparb Keawsawasvong; Bishal Chudal; Kiritharan Mahalingasivam; Sorawit Seehavong (Geosciences, 2021)
Road subsidence and sinkhole failures due to shallow cavities formed by defective water main have increased in recent decades and become one of the important research topics in geotechnical engineering. The present paper numerically studies the stability and its associated failure mechanism of ellipse-shaped cavity above defective water mains using the finite element limit analysis technique. For a wide range of geometrical parameters, the pressure ratio method is used to formulate the stability solutions in both blowout and collapse scenarios. Even though there is no published solution for elliptical cavities under blowout failure conditions, the obtained numerical results are compared with available circular solutions. Several conclusions are drawn based on the failure mechanism study of the various ellipse shape transformations in this study, whilst design charts and equations proposed for practical uses.